URGENSI DIALEKTIKA AKAL DAN WAHYU (PERSPEKTIF FAZLUR RAHMAN) DALAM PENGEMBANGAN PENDIDIKAN AGAMA ISLAM DI ERA GEN Z - Celine, Devi Rofidah; Fahmi, Muhammad; Salik, Mohamad; Lutfiyah, Siti Khumairotul; Qurratina, Noor Shania (STIT Al-Ittihadiyah Labuhanbatu Utara, 2025)
Generation Z (Gen Z) faces serious challenges in maintaining moral and spiritual identity amidst the swift flow of information, social media penetration, and academic pressures in the digital era. In this situation, Islamic religious education is required not only as a fortress of values, but also as an agent of innovation that is able to adapt to changing times. This research aims to explore the application of the dialectical principle between reason and revelation in Islamic religious education as an effort to answer the social dynamics and technological challenges faced by Gen Z. The method used is descriptive with a literature approach, through analysis of Fazlur Rahman's works and other relevant literature. The results show that Fazlur Rahman's thought, especially the concept of double movement, offers a dynamic approach to bridging the tension between religious tradition and the demands of modernity. However, the implementation of this thought in the Islamic education system is still limited and requires contextual pedagogical adaptation. In conclusion, the integration of reason and revelation in Islamic religious education is important to form Gen Z characters who are resilient, critical and religious. Innovative strategies based on digital literacy, dialogical approaches, and strengthening spiritual values are needed so that religious education remains relevant and effective in the digital era.